Experimental and clinical evaluation of a new intra-lingual suture pattern for management of lingual wounds in farm animals - Aiman M. Seddek (South Valley University, 2021)
A pre-clinical experimental study is used to evaluate a new intralingual suture pattern, for treating farm animal’s tongue-wounds. Experimental section was performed on 36 fresh goat’s tongue-samples, to compare the new suture pattern with the traditionally used two patterns (double rows simple interrupted pattern; and tension relieve vertical mattress with deep row simple interrupted pattern that is followed by superficial opposing vertical mattress). Comparison involved the required stitches number, duration of suturing, and pattern’s tensile strength. The main clinical study was carried out on recent lingual wounds of variable depths which involved 30-50% of tongue width in one horse, one camel, one buffalo-calf, and three donkeys. In addition to three donkeys had old lacerations which failed to heal by first intension. Wounds sutured by the new pattern were covered by one row of cruciate mattress to oppose the mucosa. Results revealed that the new pattern required fewer stitches numbers, consume lesser time, had higher tensile strength, it could be applied easily, achieved proper apposition of both the muscular layer and mucosa, and it induced minimal scar formation and deformity. The technique is widely acceptable by the owners than the other traditional merhods. The technique is advised to be used as alternative suture pattern for repair of lingual wounds of farm animals.